Pre-procedure endoscopic features associated with difficult cannulation in endoscopic retrograde cholangiopancreatography in a referral hospital in Lima, Peru - Quiroga-Purizaca, Wilmer Gustavo (2025)
Introduction: Several variables have been studied to predict difficult cannulation during endoscopic retrograde cholangiopancreatography (ERCP), but none have been identified that can effectively predict this difficulty and help make decisions to prevent complications. Objectives: To determine whether endoscopic variables of the duodenal papilla, as well as the sign of bile aspiration, are associated with difficult cannulation during ERCP. Materials and methods: A prospective and analytical study that included 203 patients who underwent ERCP, establishing an association between the type of duodenal papilla, location, presence of periampullary diverticulum and the sign of bile aspiration, and difficult cannulation. Results: 140 (69.97%) women and 63 (31.03%) men were included, with an average age of 54.35 years. Difficult cannulation criteria were present in 32.51% of patients. Type 1 duodenal papilla had a lower rate of difficult cannulation, while types 3 and 4 had a higher cannulation difficulty (OR=1.89, 95% CI: 1.01-3.54 and OR=4.37, 95% CI: 1.54-12.4 respectively). The distal location of the duodenal papilla had an OR=1.32 for difficult cannulation, while the presence of a periampullary diverticulum had an OR=0.54 and the endoscopic sign of bile aspiration OR=0.9, without being statistically significant. Conclusion: Types 3 and 4 duodenal papilla are significantly associated with difficult cannulation. The location of the papilla, as well as the presence of a periampullary diverticulum and bile aspiration, are not significantly associated with difficult cannulation.